Structure and bonding in crystalline materials - Rohrer, Gregory S. (Cambridge University Press, 2001)
"One of the motivating questions in materials research today is: how can elements be combined to produce a solid with specified properties? One part of the answer to this question lies in the fundamental relationship between the composition, structure and bonding in crystalline materials. This book is intended to acquaint the reader with established principles of crystallography and bonding that are needed to understand this relationship." "This book is primarily intended as an advanced undergraduate or graduate level textbook for students of materials science who are preparing to conduct research. However, it will also be useful to scientists and engineers who work with solid materials."--Jacket